Real-time embedded components and systems : with Linux and RTOS - Siewert, Sam (Mercury Learning and Information, 2016)
This book is intended to provide senior undergraduate or graduate students in electrical engineering or computer science with a balance of fundamental theory, review of industry practice, and hands-on experience to prepare for a career in the real-time embedded system industries. It is also provides practicing engineers with the necessary background to apply real-time theory to the design of embedded components and systems. New to this edition are chapters focused on key technology advancements in embedded systems with wider coverage of real-time architectures. The focus remains the RTOS (Real-Time Operating System), but use of Linux for soft real-time, hybrid FPGA (Field Programmable Gate Array) architectures and advancements in multi-core system-on-chip (SoC), as well as software strategies for asymmetric and symmetric multiprocessing (AMP and SMP) relevant to real-time embedded systems, have been added. --